Tears of a tiger - Draper, Sharon M. (Sharon Mills) (New York : Simon Pulse, 1994)
The death of high school basketball star Rob Washington in an automobile accident affects the lives of his close friend Andy, who was driving the car, and many others in the school.
Keywords: Death -- Fiction; High schools -- Fiction; Schools -- Fiction; African Americans -- Fiction; Young adult fiction